High-level recombinant human lysozyme expressed in milk of transgenic pigs can inhibit the growth of Escherichia coli in the duodenum and influence intestinal morphology of sucking pigs. - Dan Lu (Public Library of Science (PLoS), 2014)
Lysozyme is often used as a feed additive and acts as an antimicrobial protein that enhances immune function and defends against pathogenic bacteria in pigs. In this study, we genetically added recombinant human lysozyme (rhLZ) to sow milk by somatic cell nuclear transfer and investigated whether the presence of recombinant human lysozyme can influence intestinal microbiota and morphology in sucking pigs. We generated transgenic cloned pigs and the first-generation hybrids (F1) produced high levels of rhLZ in milk. The average concentration of rhLZ was 116.34 ± 24.46 mg/L in the milk of F1 sows, which was 1500-fold higher than that of the native pig lysozyme. In vitro, it was demonstrated that rhLZ in milk of transgenic pigs had enzyme levels at 92,272 ± 26,413 U/mL. In a feeding experiment, a total of 40 newborn piglets were nursed by four transgenic sows and four sibling non-transgenic sows (F1), with five piglets per gilt. The piglets were allowed to nurse for 21 days and the sow milk was the only source of nutrition for the piglets. All piglets were slaughtered on postnatal day 22. Six types of bacteria were cultured and analyzed to detect the impact of rhLZ on gut microbiota. The number of Escherichia coli in the duodenum of piglets reared by transgenic sows was significantly decreased (p<0.001) and their villus height to crypt depth ratio in the intestine were increased due to the significant decrease of crypt depth in the duodenum, jejunum, and ileum (p<0.001). Together, we successfully generated rhLZ transgenic cloned pigs and elevated lysozyme level in nuring piglets. The results of the feeding experiments demonstrated that rhLZ-enhanced milk can inhibit the growth of E. coli in the duodenum and positively influence intestinal morphology without adversely affecting weight gain or piglet growth.